Analisis Keaktifan Belajar Melalui Tipe Kepribadian Peserta Didik Pada Program Komunitas Paket B Kelas IX Di Homeschooling Kak Seto Surabaya - Siswati, Naela Putri; Riyanto, Yatim (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
Learning activities are one of the successes of optimizing the potential of learners. Each student has different learning activities that are influenced by his or her personality or character. Individual personalities are classified as 2 extroverts and introverts. The purpose of this study is to find out the learner's learning activities according to his personality type. The research methods used are qualitative descriptive using participatory observation data collection techniques, in-depth interviews, and documentation. Data analysis techniques used include data collection, data reduction, data presentation, and verification or conclusion. Results obtained from this study show that extrovert personality types favor short learning media, are active in verbal learning, have audio-verbal learning, record material when feeling needed, are bold in opinion, and have open emotional control. Introverted personality type learners like old visual learning media, like slightly verbal learning processes, have audio-visual learning, record material when feeling needed, have high memory, and have closed emotional control.